Cellulose Nanofibers from Olive Tree Pruning as Food Packaging Additive of a Biodegradable Film - Sánchez-Gutiérrez, Mónica (Foods, 2021)
A biodegradable packaging film containing cellulose nanofibers from olive tree pruning, a by-product of olives production, was obtained using a solvent casting method. Nanocellulose was added to polyvinyl alcohol (PVA) to enhance the technological properties of the composite film as food packaging material. Nanocellulose was obtained from unbleached and bleached pulp through a mechanical and TEMPO pretreatment. Crystalline and chemical structure, surface microstructure, UV and gas barrier, optical, mechanical and antioxidant properties, as well as thermal stability were evaluated. Regarding optical properties, the UV barrier was increased from 6% for the pure PVA film to 50% and 24% for unbleached and bleached nanocellulose, respectively. The antioxidant capacity increased significantly in unbleached mechanical nanocellulose-films (5.3%) compared to pure PVA film (1.7%). In terms of mechanical properties, the tensile strength of the 5% unbleached mechanical nanocellulose films was significantly improved compared to the pure PVA film. Similarly, the 5% nanocellulose films had increased the thermal stability and improved barrier properties, reducing water vapor permeability by 38–59% and presenting an oxygen barrier comparable to aluminum layer and plastic films. Our results support the use of the developed films as a green alternative material for food packaging.